Konsep Budaya Lokal pada Redesain Bangunan International Plaza Palembang dengan Studi Komparasi Bangunan Sarinah Jakarta - Karina Karina (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The central building of the cyber world in the city center plays a significant role in enhancing community activities, providing social space, and contributing to the city's image. As the first shopping center in Palembang City, International Plaza has historical and strategic value in the city's development. However, over time, the attractiveness of International Plaza has decreased significantly. This decline is caused by several factors, such as the development of new, more modern shopping centers and the lack of updates to the building's design elements that can attract visitors. This study aims to analyze the potential for redesigning International Plaza with a local cultural approach. In this redesign concept, the Sarinah Building in Jakarta is used as a comparative study because it has successfully combined modern concepts with the development of traditional elements that reflect local culture. The Sarinah Building, although designed with a modern approach, still maintains cultural values relevant to the surrounding community, thus creating a space that is not only functional but also has visual and emotional appeal for its visitors. The results of the study indicate that with a modern architectural approach that remains based on local culture, International Plaza has the potential to revitalize and attract visitors. The suggested redesign includes changes to the building's facade by adding ornaments typical of Palembang City, such as traditional carvings or motifs that reflect the richness of local culture. These ornaments can be applied using secondary skin techniques to building facades, which not only enhance aesthetics but also serve as sunscreens. Furthermore, zoning and tenant order are crucial for a more organized and comfortable visitor flow. Finally, enhancing the public space at the front of the building with additional public facilities, gardens, and gathering areas can create a more vibrant and enjoyable atmosphere for visitors.